Test The Effectiveness of the Combination of Essential Oils of Fragrant Lemongrass Leaves (Cymbopogon nardus) and Musk Orange Peel (Citrus Microcarpa) in Oil-Based Aromatherapy Candle Preparations Used Cooking Oil as a Repellnt of Aedes sp. mosquitoes - Sri Ulva Ahmad; Laksmyn Kadir; Tri Septian Maksum (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
Aedes sp. mosquitoes are the main vector of Dengue Hemorrhagic Fever (DHF) which is a public health problem. Chemical-based mosquito control efforts tend to cause resistance and environmental impacts, so safer natural alternatives are needed. This study aims to test the effectiveness of the combination of essential oils of sweet lemongrass leaves and musk orange peel in the preparation of used cooking oil-based aromatherapy candles as a repellent of Aedes sp. mosquitoes. This type of pure experimental research (true experiment) using a complete random design (RAL). The population in this study was Aedes sp. mosquitoes and a sample of 300 mosquitoes using one control and three treatments with a concentration of 10% fragrant lemongrass leaves, 10% musk orange peel, and 10% combination of both with 3 repeats for 3 hours of observation. The data was analyzed using the Anova One-Way test with an error rate (?) of 5%. The results of the study showed that aromatherapy wax preparations from essential oils of fragrant lemongrass leaves, musk orange peel and a combination of both with a concentration of 10% can kill mosquitoes 56%, 32% and 92% respectively. There is a significant difference with (p-value = 0.000<0.05). Further development of this aromatherapy wax formulation with variations in concentration is recommended to optimize its effectiveness as a repellent.